2015
DOI: 10.1186/s12866-015-0591-5
|View full text |Cite
|
Sign up to set email alerts
|

The secreted autotransporter toxin (Sat) does not act as a virulence factor in the probiotic Escherichia coli strain Nissle 1917

Abstract: BackgroundEscherichia coli Nissle 1917 (EcN) is a probiotic used in the treatment of intestinal diseases. Although it is considered safe, EcN is closely related to the uropathogenic E. coli strain CFT073 and contains many of its predicted virulence elements. Thus, it is relevant to assess whether virulence-associated genes are functional in EcN. One of these genes encodes the secreted autotransporter toxin (Sat), a member of the serine protease autotransporters of Enterobacteriaceae (SPATEs) that are secreted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 48 publications
1
25
0
7
Order By: Relevance
“…We previously showed that EcN CF-SN have a positive impact on the TER of epithelial cell monolayers and prevent barrier disruption caused by pathogens (Toloza et al, 2015). To test the ability of tcpC -positive strains ECOR63 and ECOR57 to strength the epithelial barrier, T-84 monolayers were incubated for 24 h with CF-SN (2 mg/ml) collected from LB cultures, and TER was measured before and after the treatment period.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously showed that EcN CF-SN have a positive impact on the TER of epithelial cell monolayers and prevent barrier disruption caused by pathogens (Toloza et al, 2015). To test the ability of tcpC -positive strains ECOR63 and ECOR57 to strength the epithelial barrier, T-84 monolayers were incubated for 24 h with CF-SN (2 mg/ml) collected from LB cultures, and TER was measured before and after the treatment period.…”
Section: Resultsmentioning
confidence: 99%
“…The tcpC knockout mutant derived from EcN was generated by antibiotic marker exchange using the suicide plasmid pUT-miniTn5 Tc (Biomedal) as described previously (Toloza et al, 2015). This vector contains the R6K origin of replication, which functions only in bacteria that contain the gene pir .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations